CNT spacer-induced cooling crystallisation: a novel approach to mitigate membrane scaling in membrane distillation without chemicals - Seongeom Jeong; Boram Gu; Gyeong Hwan Choi; Chae Bin Kim; Sanghyun Jeong (npj Clean Water)
Abstract Membrane technology is crucial for water treatment as it effectively separates and rejects pollutants. However, its industrial application is often limited by membrane scaling and fouling issues, which degrade membrane performance and affect the efficiency and longevity of membrane systems. Our previous study demonstrated that a 3D-printed carbon nanotube (CNT) spacer improved membrane performance by increasing the membrane flux and controlling scaling in membrane distillation. Here, we present a detailed mechanism by which a CNT spacer mitigates membrane scaling by inducing cooling crystallisation. The CNT spacer delayed crystallisation and reduced crystal adhesion on both the membrane and spacer surfaces. Additionally, the presence of the CNT spacer resulted in the formation of larger crystals that are less likely to adhere to surfaces. The nanoscale roughness and nanochannels created by the exposed CNT in the spacer appeared to strengthen hydrogen bonding within the solution, further delaying crystallisation and reducing crystal adhesion. These findings were corroborated by comparing the experimental observations with theoretical predictions derived from our mechanistic model, providing a comprehensive understanding of the scaling mitigation process. Our approach addresses several limitations of membrane technology, enhancing performance and reducing scaling and fouling risks, paving the way for broader application in water treatment.